Analytical modeling of power transfer via metallic nanoparticles in a solar cell absorber. (March 2020) - Singh, Bhaskar; Shabat, Mohammed M.; Schaadt, Daniel M.
Highlights: Light scattering and absorption in metallic nanoparticles are studied with Mie theory. A TMM based analytical model for power transfer from nanoparticle layer into a solar cell absorber is developed. Metal nanoparticles with an absorber layer is studied. Al-nanoparticles based proposed structure demonstrates higher power transfer than Ag-, Au-, and Cu-nanoparticles. Au-, and Cu-nanoparticles show high backscattering in visible region. Abstract: Metallic nanoparticles scatter sun light efficiently at resonance wavelength where the scattering and absorption in the nanoparticles are highly influenced by shape, size, material composition, host medium, and volume fraction of the nanoparticles in the host medium. We present transfer matrix method and Mie theory based a modified analytical model to optimize the scattering property of nanoparticles and to simulate power transfer from the metallic nanoparticles (Ag, Au, Cu, and Al) layer into an absorber layer ( n -GaAs). We compare the performance of nanoparticles with bare n -GaAs layer. We found that Al-nanoparticles based structures show higher power transfer in the absorber layer than Ag, Au, and Cu nanoparticles.